2014
DOI: 10.1167/iovs.14-13957
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Plastic Lamina Cribrosa Displacement in Glaucoma Patients

Abstract: PURPOSE.To investigate factors associated with irreversible components of anterior lamina cribrosa (LC) depth in glaucoma patients. METHODS.A total of 141 glaucoma patients and 51 healthy control subjects were enrolled. The optic nerve head (ONH) was imaged using the enhanced depth imaging (EDI) modes of Spectralis optical coherence tomography (OCT). The depth of the LC was measured at the midhorizontal, superior, and inferior midperipheral regions of the ONH of each eye. Analyzed factors associated LC depth i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…[34][35][36] We also found that LC depth was correlated with initially untreated IOP in our previous study. 37 IOP reduction reverses the posterior displacement of the LC. 4,38,39 Optic disc morphological characteristics of the eyes without a focal LC defect included generalized rim enlargement, which may also be related to the deep LC depth from a high IOP.…”
Section: Discussionmentioning
confidence: 92%
“…[34][35][36] We also found that LC depth was correlated with initially untreated IOP in our previous study. 37 IOP reduction reverses the posterior displacement of the LC. 4,38,39 Optic disc morphological characteristics of the eyes without a focal LC defect included generalized rim enlargement, which may also be related to the deep LC depth from a high IOP.…”
Section: Discussionmentioning
confidence: 92%
“…4 In particular, glaucomatous onset is associated with posterior displacement of the anterior LC surface, 5-7 posterior migration of the LC insertion points, 6 and backward bowing of the entire LC. 8 Nonhuman primate models of glaucoma have also shown similar associations.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on the association between age and LC parameters have included large numbers of patients with high tension glaucoma or ocular hypertension. 36,38 By contrast, Rho et al 39 found no significant correlation between age and LCD in a group of normal tension glaucoma patients. The majority (36 of 41) of the glaucoma patients in the present study, moreover, were POAG patients with untreated IOP 21 mm Hg.…”
Section: Discussionmentioning
confidence: 93%
“…Acute IOP elevation was positively associated with prelaminar tissue displacement but not with laminar displacement in an experimental in vivo study of glaucoma patients and healthy controls. Jung et al, 36 after demonstrating a positive correlation between initial IOP and LCD (r ¼ 0391, P < 0.001) in glaucoma patients, suggested that initial IOP is the most decisive factor for LC displacement. Zhao et al, 37 in an animal study using cats, showed that as IOP increased, the thicknesses of both the LC and prelaminar tissue decreased and, further, that the thickness variation of the LC correlated significantly with the IOP increase when the IOP was higher than 60 mm Hg.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation